Citopatologia causada pelo Alphabaculovirus no sistema traqueal de Bombyx mori (Lepidóptera: Bombycidae) - Madureira, Jéssica Vencatto Senem (2014)
Bombyx mori is an insect of the order Lepidoptera that is only found only in germplasm banks; it is used in scientific research and for commercial purposes. In the latter case, the silk cocoon, which is produced at the end of the 5th larval instar, is used in the production of various yarns and fabrics. This branch of Brazilian agribusiness, known as sericulture, is well developed in the state of Paraná, where it is a form of small-scale family farming. Several factors impact negatively on Brazilian sericulture, such as diseases during rearing, and B. mori is susceptible to a virus from the Baculoviridae family, namely, Bombyx mori multiple nucleopolyhedrovirus (BmMNPV), genus Alphabaculovirus (AlphaBV), which infects the larvae and jeopardises commercial production of the cocoon, causing losses to farmers and industry. Studies have proved that BmMNPV is polyorganotropic and there are several target organs, such as the tracheal system; however, details of its cytopathology are not known. The tracheal system is responsible for the aeration of the tissues of the insect. Thus, the present study aimed to describe the cytopathology of the tracheas of hybrid larvae of B. Mori, infected experimentally with BmMNPV, and isolated geographically in the state of Paraná. Fifth instar hybrid larvae were divided into two groups; one control, and the other inoculated. After ingestion, and on different days post-inoculation (dpi), from the 2nd to the 9th dpi, the larvae were anesthetized and dissected. Segments of organs such as the integument, muscle and silk gland, containing branches of the trachea, were collected and fixed in Karnovsky modified for transmission electron microscopy. On the 2st dpi, fresh hemolymph analysis was conducted in order to determine the susceptibility of the hemocytes. The results revealed that the hemocytes were infected from the 2nd dpi and the epithelial cells of the trachea were infected from the 4th dpi. The cytopathology of the tracheal cells showed hypertrophic nucleus, containing the viroplasm, the site of the synthesis of the nucleocapsids. Subsequently, the formation and development of the polyhedra occured, accentuating the nuclear hypertrophy and culminating in cell lysis. Virions were also observed, immersed in the basal lamina of the trachea, which appeared to be disorganized. Thus, the cytopathology of the trachea was consistent with the infection caused by AlphaBV, and the data that was obtained provides a better understanding of the infectious cycle of BmMNPV in the body of the insect. The time of infection, later for the hemocytes, and the presence of virions in the basal lamina of the trachea, indicated that this system is a secondary target for infection, and also that the hemolymph is an important dispersant of viral infection